In vitro regeneration of pineapple (Ananas comosus) variety MD2 using different concentrations of BAP and NAA / Siti Aisyah Othman - Othman, Siti Aisyah (Faculty of Plantation and Agrotechnology, 2015)
Pineapple is the third most important fruits in the world that have high demand usually for food consumption, which can be propagated traditionally and through in vitro technique. In vitro regeneration of pineapple variety MD2 was carried out using different concentrations of BAP and NAA and to determine the best concentration that can give the best result to produce MD2 pineapple disease free. Ten different concentrations of BAP and NAA were applied into MS solid media. The parameters collected are; number of shoots per explant, length of shoots, length of plantlet and fresh weight of plantlet were collected and recorded weekly. The data was analyzed by using Minitab 16.1 and Microsoft Excel software. The results obtained in this experiment indicated that there is significant difference in the number of shoots per explant, length of shoots, length of plantlet and fresh weight of plantlets. An optimum concentration of BAP and NAA found from this study was at 2.5 mg/L BAP combine with 0.25 mg/L NAA. It gave highest mean value in number of shoot, length of shoot, length of plantlet and fresh weight of plantlet. However, ANOVA of the experiment shows that there is no significant different between each treatment.